การใช้ความรุนแรงในการเคลื่อนไหวคัดค้านการเปิดดำเนินงานของโรงงานไทยแลนด์แทนทาลัมอินดัสตรี จังหวัดภูเก็ต - สหชัย แจ่มประสิทธิ์สกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research is to study the conditions that lead to violence in the protest against the opening of the Thailand Tantalum Industry Factory in Phuket province. This study confines within the political, economic, and social contexts of Phuket from the pre-protest period to its ending. The hypothesis is that the conditions leading to violence are based on the observation that violence is used as a means to achieve the goal rather than the dissatisfaction or anger caused by frustration from the risk of severe pollution in the future that could affect the people s lives. The data was gathered from the documents related to the event, the supreme court verdict, witness testimonies, and the interviews with the former protesters. The findings of the study indicate that the violence happened in the situation of poorly organized and unprepared mass demonstration. The conditions that lead to the use of violence in this case are the lack of progress in conflict resolution, the condition of inefficient communication in the mass demonstration, and the psychological conditions among the mass as a result of unclear situations.